ANALISIS KESULITAN DAN STRATEGI GURU DALAM MELAKSANAKAN PENILAIAN PEMBELAJARAN PADA MASA COVID-19 DI SEKOLAH DASAR - Adya Pribadi, Reksa; Nurhasanah, Ana; Salsabila Rahayu, Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
The purpose of this research is to find out the difficulties and strategies of teachers in carrying out learning assessments during the Covid-19 period in elementary schools. The type of research conducted is descriptive qualitative where research that describes the research subject qualitatively means that the data collected are in the form of words or pictures. This research was conducted in one of the elementary schools in Tanggerang district, namely SDN Renged 3. From the results of the study the difficulties of teachers in carrying out assessments during the COVID-19 pandemic, namely the limitations of face-to-face learning, conducting affective and psychomotor assessments and finally the limitations of students in participating in learning activities. online learning (in the network). And the strategy used by the teacher in carrying out the assessment is by giving assignments, holding face-to-face learning in turns and from the craft of students.